2021
DOI: 10.3390/ijms22052547
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL Mediates Neuronal Death in AUD: A Link between Neuroinflammation and Neurodegeneration

Abstract: Although the cause of progressive neurodegeneration is often unclear, neuronal death can occur through several mechanisms. In conditions such as Alzheimer’s or alcohol use disorder (AUD), Toll-like receptor (TLR) induction is observed with neurodegeneration. However, links between TLR activation and neurodegeneration are lacking. We report a role of apoptotic neuronal death in AUD through TLR7-mediated induction of death receptor signaling. In postmortem human cortex, a two-fold increase in apoptotic terminal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 92 publications
(98 reference statements)
8
38
0
Order By: Relevance
“…and RELA in the OFC, consistent with TLR coupling to MyD88 activating the proinflammatory nuclear factor NFκB and downstream transcription of proinflammatory signaling molecules (Kawai & Akira, 2007;Pahl, 1999;Schmitz & Baeuerle, 1991). Indeed, we previously reported that AUD increases activated pRELA+IR in the human OFC (Qin et al, 2021), consistent with activation of NFκB.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…and RELA in the OFC, consistent with TLR coupling to MyD88 activating the proinflammatory nuclear factor NFκB and downstream transcription of proinflammatory signaling molecules (Kawai & Akira, 2007;Pahl, 1999;Schmitz & Baeuerle, 1991). Indeed, we previously reported that AUD increases activated pRELA+IR in the human OFC (Qin et al, 2021), consistent with activation of NFκB.…”
Section: Discussionsupporting
confidence: 79%
“…NFKB2, RELB, and REL were unchanged between groups. Increases of NFKB1 and RELA are consistent with activation of NFκB transcription, and we previously reported increased activated pRELA+IR in the postmortem human AUD OFC relative to CONs (Qin et al, 2021). We extend those findings with colocalization of pRELA+IR with Iba-1+IR microglia, GFAP+IR astrocytes (Figure S1C,D), and NeuN+IR neurons (Figure 2D), consistent with NFκB activation across cell types within the AUD OFC.…”
Section: Increased Expression Of Nfκb Family and Signaling Genes In The Postmortem Ofc Of Individuals With Audsupporting
confidence: 88%
See 2 more Smart Citations
“…An area that has gained considerable attention is the role that the innate immune or neuroimmune system plays in the development and maintenance of alcohol use and abuse (Blednov et al, 2012;Crews et al, 2017a;Crews et al, 2013;Erickson et al, 2019;Mayfield et al, 2013). Studies in postmortem human brain tissue find that proinflammatory signaling molecules are increased in AUD (Coleman et al, 2017;Crews et al, 2013;Crews and Vetreno, 2014;Crews et al, 2016;Crews et al, 2017b;Qin and Crews, 2012;Qin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%